Thermal–mechanical modelling of laminates with fire protection coating - Mouritz, A.P.; Feih, S.; Kandare, E.; Gibson, A.G. (Composites. Part B, Engineering, 2013)
This paper presents a modelling approach to analyse the protection provided by passive and intumescent surface coatings on glass fibre reinforced laminate substrates exposed to fire. The modelling involves a multi-stage analytical approach: (i) thermal analysis of heat transfer from the fire through the surface insulation coating, which includes decomposition and expansion in the case of an intumescent material; (ii) thermal–chemical analysis of heat transfer through the fibreglass laminate substrate (beneath the fire protective coating), including decomposition of the polymer matrix; and (iii) thermal–mechanical analysis of softening and failure of the laminate under in-plane tension or compression loading. The modelling approach is validated using experimental temperature and strength data from fire structural tests performed on woven glass–vinyl ester laminates insulated with passive (ceramic fibre mat) or organic intumescent surface coatings.